2019
DOI: 10.1002/bjs.11140
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of totally extraperitoneal inguinal hernia repair in patients with previous lower abdominal surgery

Abstract: Background: Previous lower abdominal surgery is considered a relative contraindication to laparoscopic totally extraperitoneal (TEP) inguinal hernia repair. This was a meta-analysis of studies comparing the feasibility and safety of TEP repair between patients with (PS), and without (NS) a history of lower abdominal surgery. Methods: A systematic literature search was undertaken for studies comparing the outcome of TEP inguinal hernia repair in patients with, and without previous lower abdominal surgery. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
(46 reference statements)
1
9
1
Order By: Relevance
“…TEP repair is a relative contraindication for patients who have had lower abdominal surgery because access to the preperitoneal space and safe dissection may be difficult because of scar tissue from previous surgeries. 1,10,15,22 There 10 Elshof et al 23 reported a 9.8% conversion rate in TEP surgery for right inguinal hernia in patients who underwent open appendectomy. Lau and colleagues found a conversion rate of 4.3% and a PT rate of 56.5% in patients who underwent open appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…TEP repair is a relative contraindication for patients who have had lower abdominal surgery because access to the preperitoneal space and safe dissection may be difficult because of scar tissue from previous surgeries. 1,10,15,22 There 10 Elshof et al 23 reported a 9.8% conversion rate in TEP surgery for right inguinal hernia in patients who underwent open appendectomy. Lau and colleagues found a conversion rate of 4.3% and a PT rate of 56.5% in patients who underwent open appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The chances of peritoneal tear become higher in case of preexisting scarring as a result of lower abdominal surgery, a factor that has been shown to generally result to a worse outcome in general, compared to cases with a virgin pre-peritoneal envelope. [24] Cases with previous lower abdominal surgery were excluded in 3 of the meta-analyzed RCTs. [13][14][15] The second most common intraoperative morbidity reported was major bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proposed simultaneous inguinal hernia repair and prostatectomy through two different independent surgical cuts and not using the retroperitoneal mesh. 12–16 An inguinal hernia repair concomitant with prostatectomy was firstly reported by McDonald and Huggins, however this was performed with two separate incisions, with the hernia defect repaired through the inguinal approach. 1719 After that, the Pfannenstiel-Kerr incision or pubic incision, that allows access to the abdomen, was suggested for the hernia repair meanwhile performing a simple prostatectomy.…”
Section: Discussionmentioning
confidence: 99%